16 Standardized phytomolecules improve foot and mouth disease vaccine response in grower pigs. (5th December 2019) - Blanchard, Alexandra; Grandmaison, Josselin le Cour; Kim, In Ho; Kim, Yong Min
Abstract: Foot and Mouth Disease (FMD) is a severe viral disease with significant economic impact. In endemic countries, livestock may be vaccinated. Standardized capsicum and turmeric oleoresins have demonstrated a boosting effect of vaccination in broiler, but little is known on their efficacy in swine. The objective of this trial was to evaluate the efficiency of these phytomolecules to improve FMD vaccine response in pigs. Cross-breed pigs (n = 120) with body weight of 24.6 kg were allotted into 3 groups of 40 pigs and assigned into 10 replicates from days 70 to 112 of age. Following treatments were applied: NS: no vaccination; FMD-NS: FMD vaccination; FMD-XT: FMD vaccination + supplementation of XT-N (4% capsicum + 4% turmeric oleoresins, Pancosma, Switzerland) at 125 g/ton in feed. The FMD vaccine (Omanisa + O3039 + A22 Iraq-strain, Merial) was injected at day 78. Blood samples were collected at days 88, 93, 98 and 103 to evaluate antibody levels. Growth performance was evaluated at day 112. Data were analyzed using the GLM procedure of SAS®. During the trial, non-vaccinated pigs (NS) did not display antibody titers against FMD, but vaccinated pigs (FMD-NS and FMD-XT) exhibited significant levels of FMD antibodies (P < 0.05). Pigs of FMD-XT group showed significant higher antibody levels at day 93 (P < 0.05), day 98 (P = 0.06) and day 103 (P < 0.05) in comparison to FMD-NS pigs. It indicated significant improvement of FMD vaccine response in comparison to the vaccinated control. At 112 days, FMD-NS pigs were numerically lighter (53.46 kg) in comparison to non-vaccinated pigs (53.89 kg). However, FMD-XT pigs were heavier (54.51 kg) in comparison to NS pigs (+0.62 kg, P >0.05) and FMD-NS pigs (+1.05 kg, P < 0.05). These findings showed that standardized phytomolecules (XT-N) incorporated into pig diet significantly supported FMD vaccination response and alleviated its negative effect on growth.